(3GdCeKGd aj ecGQe GdGNdGbs
(3ChdgG (B:s
(3bGd GHh YHjO ef GeKGdge ai GdMde GPG fRd Hc GdTQ aGbYO aGMde hdG eJSGQY s
(3BNQgG (B:s
(3hcGf Sgd ef gGQhf jbhd ai JZQjJg GPG YRi GdjefjI HCLd GdKhGH ChLH ef GdJYRjI Ydi YGLd GdeUjHI Je cJGH GdOQI s
(3Vef eLehY , JQJjHgG (B: 1s
(3Hdjg bWYI ef cJGH GdbdGFO hGdaQGFO ai CMcGe GdSjGSI ddKYGdHis
(3ai GhQGbI GVWQGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdSjO eMeO Hf eMeO Hf GSeGYjd GdeWgQ HUfYGA (B((3NGU(B) s
Keywords: (3eJaQbGJs